Emissions of Carbon, Nitrogen, and Sulfur from Biomass Burning in Nigeria - Akeredolu, Funso; Isichel, A. O. (2014)
There are as yet no reported direct measurements of emissions of carbon, nitrogen, and sulphur in the Nigerian environment. Extrapolations here have been based on the composition of the sources before burning. The accuracy of the analysis of the chemical compositions of the vegetations is, however, not in doubt, so that at their face value, the estimates are fairly reliable. Most estimates have been pantropical and therefore involve extreme generalizations. The present estimates will help in arriving at better global estimates. There are however, some assumptions made which would need to be validated through further experimentation.